2019
DOI: 10.37358/mp.19.1.5167
|View full text |Cite
|
Sign up to set email alerts
|

Biochemistry in Assessing the Inflammatory Response of the Respiratory System Due to Experimental Exposure to Glass Fibres

Abstract: Given the structural resemblances between glass fiber and asbestos, it is important to understand the mechanisms through which exposure to glass fibers may affect the respiratory system. To study the effect of glass fiber on rat lung through intratracheal exposure, considering the subject�s weight variation, together with haematological parameters, C-reactive protein (CRP), total number of lymphocytes, and IL8 concentration in bronchoalveolar lavage. We performed an intratracheal instillation study on four gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The lung microbiome evaluation studies were based on the analysis of bronchoalveolar lavage obtained by bronchoscopy [1]. This technique is widely used to study and highlight the pathogenetic mechanisms and inflammatory response through the influx of proinflammatory cells [7]. Although sputum examination is a less invasive method compared to bronchoscopy, it presents an increased risk of contamination when passing through the oropharyngeal cavity [1].…”
Section: Discussionmentioning
confidence: 99%
“…The lung microbiome evaluation studies were based on the analysis of bronchoalveolar lavage obtained by bronchoscopy [1]. This technique is widely used to study and highlight the pathogenetic mechanisms and inflammatory response through the influx of proinflammatory cells [7]. Although sputum examination is a less invasive method compared to bronchoscopy, it presents an increased risk of contamination when passing through the oropharyngeal cavity [1].…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 ] Also, it has been reported that processing GFs pose serious health related issues. The inhalation of glass fiber dust lead to lung cancer, [ 23 ] while it is absorption through the skin causes eczema/fiberglass dermatitis. [ 24 ] Such type of health hazards can be mitigated through the use of natural BFs.…”
Section: Introductionmentioning
confidence: 99%